2023
DOI: 10.3389/fpubh.2023.1168077
|View full text |Cite
|
Sign up to set email alerts
|

The influence of neighborhood built environment on school-age children’s outdoor leisure activities and obesity: a case study of Shanghai central city in China

Abstract: ObjectiveThe aim of this study was to examine the influencing pathways of the neighborhood built environment on children’s outdoor leisure activities and obesity.MethodsA total of 378 elementary school students from 10 schools in central Shanghai were selected by a convenient sampling method for questionnaire survey and accelerometer tracking.Results1) The neighborhood built environment could affect children’s obesity not only through direct effect (β = 0.15, p < 0.05), but also through the mediating ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In our study, patients faced limitations in their ability to exercise during confinement due to a lack of space, their physical condition, or a lack of company. This factor highlights a difficulty that many children and adolescents with obesity face, even in other conditions before the pandemic, as made clear by Tan and collaborators in a Chinese population; they showed that access to public spaces in the urban environment influences the individual health of these patients [13].…”
Section: Discussionmentioning
confidence: 88%
“…In our study, patients faced limitations in their ability to exercise during confinement due to a lack of space, their physical condition, or a lack of company. This factor highlights a difficulty that many children and adolescents with obesity face, even in other conditions before the pandemic, as made clear by Tan and collaborators in a Chinese population; they showed that access to public spaces in the urban environment influences the individual health of these patients [13].…”
Section: Discussionmentioning
confidence: 88%